Evaluation of lake eutrophication under different hydrological connectivity conditions - Jutao Liu; Chunyun Wen; Fang Hu; Xinyuan Liu; Dawen Zhang (Journal of Freshwater Ecology)
Lake eutrophication has become a significant water environmental issue worldwide. In order to further explore the mechanism of hydrologic connectivity on lake eutrophication and effectively control it, this study selected Poyang Lake, Junshan Lake, Chi Lake, Taibo Lake, and Yao Lake with varying degrees of hydrological connectivity in the Poyang Lake region as research subjects. The study utilized the comprehensive Trophic Level Index (TLI) method to assess the eutrophication of lakes. It also examined the impact of hydrological connectivity on eutrophication evaluation indices and the eutrophication state on a spatiotemporal scale. The results showed that the change in the hydrological period has little effect on the eutrophication of lakes, whether they are connected or obstructed. Except for Yao Lake, which was in a moderately eutrophic state (60, 70], the other four lakes were in a mildly eutrophic state (50, 60], consistent with the Trophic State Index (TSI) evaluation results. The eutrophication evaluation indices of obstructed lakes were significantly different from those of river-connected lakes. The change in eutrophication evaluation index of obstructed lakes was more likely to be influenced by human factors, whereas that of rivers-connected lakes was closely associated with hydrological connectivity. At present, there is a risk of a cyanobacteria bloom outbreak in Poyang Lake and its surrounding lakes. Therefore, this study suggests that strict control of point and non-point source pollution in the lake region, along with the scientific and reasonable formulation of a cultivation model, will effectively prevent lake eutrophication and cyanobacteria bloom outbreaks. This study provides theoretical support for investigating the mechanisms of lake eutrophication.